Analisis Antropometri dan Kecepatan Renang Atlet Klub Renang Haruna - Randyka Aziz Ramadhan; Fajar Awang Irawan (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to analyse anthropometry in relation to the speed of 50-metre freestyle swimming among athletes at Haruna Swimming Club. The subjects in this study were 15 adolescent athletes aged 12 to 15 years. Materials and methods. The research method used was a quantitative approach with multiple linear regression analysis. The independent variables analysed included height, weight, arm length, leg length, and hand width. The dependent variable was the time taken to swim the 50-metre freestyle, measured in seconds. Results. The analysis results showed that, simultaneously, all five anthropometric variables significantly influenced swimming speed (p < 0.05). Partially, arm length, leg length, and palm width showed a significant negative influence on swimming time, meaning that the larger the value of these variables, the faster the swimming time achieved. Conclusion. The conclusion of this study states that body characteristics or anthropometry play an important role in determining swimming performance in adolescent athletes. These findings can be used as a basis for athlete selection and the development of training programmes based on physical characteristics